Conduct disorder symptomatology is associated with an altered functional connectome in a large national youth sample. (14th October 2022) - Tillem, Scott; Conley, May I.; Baskin-Sommers, Arielle
Abstract: Conduct disorder (CD), characterized by youth antisocial behavior, is associated with a variety of neurocognitive impairments. However, questions remain regarding the neural underpinnings of these impairments. To investigate novel neural mechanisms that may support these neurocognitive abnormalities, the present study applied a graph analysis to resting-state functional magnetic resonance imaging (fMRI) data collected from a national sample of 4, 781 youth, ages 9–10, who participated in the baseline session of the Adolescent Brain Cognitive Development SM Study (ABCD Study®). Analyses were then conducted to examine the relationships among levels of CD symptomatology, metrics of global topology, node-level metrics for subcortical structures, and performance on neurocognitive assessments. Youth higher on CD displayed higher global clustering (β = .039, 95% CIcorrected [.0027 .0771]), but lower Degreesubcortical (β = −.052, 95% CIcorrected [−.0916 −.0152]). Youth higher on CD had worse performance on a general neurocognitive assessment (β = −.104, 95% CI [−.1328 −.0763]) and an emotion recognition memory assessment (β = −.061, 95% CI [−.0919 −.0290]). Finally, global clustering mediated the relationship between CD and general neurocognitive functioning (indirect β = −.002, 95% CI [−.0044 −.0002]), and Degreesubcortical mediated the relationship between CD and emotion recognition memory performance (indirect β = −.002, 95% CI [−.0046 −.0005]). CD appears associated with neuro-topological abnormalities and these abnormalities may represent neural mechanisms supporting CD-related neurocognitive disruptions.